The importance of the performance of the Dental Surgeon in Primary Care: a bibliographic review (Research, Society and Development, 2022)
Since 2000, with the entry into the Family Health Strategy and the Oral Health Teams (EqSB) in Brazil, the Dental Surgeon (CD) began to be part of this group. For this to happen, some changes were necessary: The dentist needed to leave his private and restricted office to meet a new clientele, who demand oral care, which promotes actions aimed at the patient's health. In view of the above, the present research aimed to carry out a bibliographic investigation regarding the relevance of the performance of Dental Surgeons in Primary Care in the Unified Health System. Therefore, works between the years 2018 to 2022 were analyzed in databases such as Google Scholar, SciELO, Lilacs and Bireme, searching for the following descriptors: Basic Health Unit (UBS); Performance of the Dental Surgeon; Relevance of the dental surgeon in health centers. After the dynamic, analytical, and critical reading of the selected studies, it was legitimate to emphasize the relevance of the inclusion and performance of the Dental Surgeon in the ESFs, operating as a member of the team in the materialization of the idea of integral health, optimizing both preventive and curative techniques, in addition to support in multidisciplinary tasks. In this way, it is concluded that it is essential that the Dental Surgeon effectively participates in the UBSs, since this specialist plays a fundamental role in the prevention of diseases.